An application of metric system in determination of gender from lateral Lip prints - Amit Chauhan (Forensic Science Today - Peertechz Publications, 2020)
In the modern era of advancement, new scientific technologies have taken over the traditional methods of investigation. Expansion of recent investigative techniques and sources have made the investigation more specific to an individual/suspect in forensic field. Since when DNA has been explored an unequivocal to an individual, since then, DNA fingerprinting have become probably the most common technique in the context of fast and reliable identification purpose [1]. Yet another aspect such as palmar surface, planter surface, labial mucosa etc. are also valuable form of evidences which are considered exclusive, perpetual, and ubiquitous by nature. These evidences have proven their feasibility in the field of investigation.